2020
DOI: 10.1371/journal.pone.0235423
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of fluopyram applied by chemigation on controlling eggplant root-knot nematodes (Meloidogyne spp.) and its effects on soil properties

Abstract: The root-knot nematode ( Meloidogyne spp.) is one of the major challenges in eggplant ( Solanum melongena L.) production. Fluopyram, known to be an effective fungicide, is also used for controlling root-knot nematode. However, in China, little information is currently available regarding the efficacy of fluopyram via chemigation against root-knot nematode and its effects on soil properties. For this, the objective of this work was to test mortality of root-knot nem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“… Faske and Brown (2019) showed that the greatest effect of fluopyram on M. incognita mortality was up to 10 cm deep in sandy soil. Li et al (2020) then reported that fluopyram was most effective against Meloidogyne spp. at concentration of 60 g·ha −1 a.i.…”
Section: Discussionmentioning
confidence: 99%
“… Faske and Brown (2019) showed that the greatest effect of fluopyram on M. incognita mortality was up to 10 cm deep in sandy soil. Li et al (2020) then reported that fluopyram was most effective against Meloidogyne spp. at concentration of 60 g·ha −1 a.i.…”
Section: Discussionmentioning
confidence: 99%
“…Because the low water solubility and strong affinity of fluopyram to soil particles typically reduces movement into the upper 10 cm soil layers [16], we hypothesize that a targeted application of fluopyram in the planting hole will have reduced side effects on beneficial organisms and the soil microbial community [25,26]. Furthermore, a wide field application of fluopyram may not have sufficient RKN control, since RKN populations are found in similar amounts at both 0-30 cm and 30-60 cm soil depths [27], generally where plant roots and moist soil are present [28].…”
Section: Application Of Fluopyram As Planting Hole Treatmentmentioning
confidence: 99%
“…This research aims to study the role of root-knot R genes in S. aculeatissimum and its potential presence in responses to M. incognita disease. With the growing usage of greenhouses for eggplant production, the concerns regarding RKNs are getting extremely serious (Li et al, 2020), and developing disease-resistant cultivars becomes an efficient and necessary way to combat associated diseases. Yang et al (2014) concluded that in S. torvum, the whole disease tolerance phase is amplified, consequently improving plant defense mechanisms and resistance survival as compared to tomato and potato.…”
Section: Resistance In the Cultivated And Wild Sourcesmentioning
confidence: 99%